PENDAMPINGAN PKM BAGI MAHASISWA DI PRODI PENDIDIKAN SEJARAH UNIVERSITAS JAMBi - Adi Saputra, Muhammad; Wahyuni, Anny; Robbi Kurniawanti, Merci (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
The Student Creativity Program (PKM) is to prepare future-oriented human resources so that they become superior, competitive, adaptive, flexible, productive and competitive graduates with the character of Pancasila and guide students to become individuals who know and obey the rules, creative and innovative as well as objective, cooperative in building intellectual diversity. Student participation in PKM in the History education study program is still small so that assistance is needed so that students have the motivation to participate in PKM. This assistance is carried out using the FGD method with the results of students understanding the types of PKM and knowing the impact and benefits of participating in the Student Creativity Program..